The Relationship Between Nurse Burnout and Patient Safety Culture with The Quality of Nursing Care in Type B Hospitals in Central Sulawesi - Susanti, Fitria Dewi; Andarini, Sri; Putra, Kuswantoro Rusca (Syntax Corporation Indonesia, 2024)
The hospital provides health services such as inpatient, outpatient, and emergency departments. The quality of nursing care is crucial as patients rely on nurses to address their complaints. This study aims to determine the relationship between nurse burnout and patient safety culture with the quality of nursing care. An analytical observational design with a cross-sectional study approach was conducted in two Type B Hospitals in Central Sulawesi Province with 235 nurse respondents in the inpatient room, using purposive sampling. Data analysis included the Pearson product-moment test and multivariate modeling. Results indicated a significant relationship between nurse burnout and nursing care quality (p-value <0.05), as well as between patient safety culture and nursing care quality. The dominant variable related to the quality of nursing care was patient safety culture (β = 0.723). The study highlights that nurse burnout negatively impacts the quality of nursing care, whereas a strong patient safety culture improves it. Theoretically, this research expands the understanding of the interplay between nurse burnout, patient safety culture, and nursing care quality, emphasizing the need for organizational support and effective communication. Practically, it suggests that hospital administrators should implement strategies to reduce nurse burnout and foster a positive patient safety culture, such as stress management programs and a supportive work environment, to enhance nursing care quality and improve patient outcomes.